Pengaruh Think Paire Share, Think Pair Square, Konvensional Terhadap Kemampuan Membaca Iqro dan Hasil Belajar - Nurdiyanto Nurdiyanto; Rahayu Kariadinata; Adam Malik (Fakultas Tarbiyah Institut Agama Islam Bani Fattah Jombang, 2024)
Abstract: The aim of this research is to describe; (1) Differences in the application of learning models (TPS, TPSq, and Conventional) to PAI learning outcomes; (2) Knowing Iqra's reading ability in terms of the economic factors of the student's parents in categories (Upper, Middle and Lower); (3) Seeing whether there is an interaction between the learning model and Iqra's reading ability in determining PAI learning outcomes. The approach taken in this research uses a quantitative approach with a quasi-experimental method. The population of this study was grade 1 students at SDIT Nur El-Qolam Serang Banten consisting of 76 students. The instruments used consist of; (1) the test determines PAI learning outcomes through a questionnaire with a questionnaire of 25 questions, including; 20 PG and 5 Essays. (2) test the ability to read Iqra through an oral test, namely reading the book Iqra volume 2. The data analysis technique in this research uses two-way ANOVA analysis. The results of this research show that; (1) There are differences in student PAI learning outcomes based on learning models (TPS, TPSq, and Conv); (2) There is no difference in student PAI learning outcomes based on Iqra reading ability in terms of the economic factors of the students' parents categories (Upper, Middle and Lower); (3) And there is no interaction between the Learning Model and Iqra reading ability in determining Student PAI Learning Outcomes.